2007
DOI: 10.1534/genetics.106.064329
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Gene Duplications in Saccharomyces cerevisiae

Abstract: Gene duplication can occur on two scales: whole-genome duplications (WGD) and smaller-scale duplications (SSD) involving individual genes or genomic segments. Duplication may result in functionally redundant genes or diverge in function through neofunctionalization or subfunctionalization. The effect of duplication scale on functional evolution has not yet been explored, probably due to the lack of global knowledge of protein function and different times of duplication events. To address this question, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
160
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(181 citation statements)
references
References 51 publications
20
160
1
Order By: Relevance
“…Thus, a new feature could emerge immediately, augmenting or modifying previous function. The possibility that duplicated genes are not redundant is supported by a number of evolutionary studies (25,53). This is not to say that large-scale gene expression given a gene duplication event must be the norm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a new feature could emerge immediately, augmenting or modifying previous function. The possibility that duplicated genes are not redundant is supported by a number of evolutionary studies (25,53). This is not to say that large-scale gene expression given a gene duplication event must be the norm.…”
Section: Discussionmentioning
confidence: 99%
“…In some instances, gene copy number is integrated into dynamic models of regulation to account for cell-to-cell variability of regulatory elements found on plasmids (23). More commonly, recent studies have attempted to identify statistical relations between CNV and fitness (4), protein interactions (24), or combinations of both (25). To understand the progression from CNV to changes in phenotype to changes in fitness, it seems necessary to carefully examine gene regulation itself.…”
mentioning
confidence: 99%
“…Several studies have shown that the mode of duplication (WGD vs. SSD) has different effects on the evolution of the genome (7,41,42). Because SSDs occur continuously and at various times, it is not possible to repeat the evolutionary analysis that was possible for the WGD.…”
Section: Posttranslational Modifications In General and Not Only Phosmentioning
confidence: 99%
“…In addition to the discovery that WGD duplicated genes are functionally biased (Blanc and Wolfe, 2004;Seoighe and Gehring, 2004;Aury et al, 2006;Freeling, 2008;Wu et al, 2008;Schnable et al, 2009), several gene features were identified to associate with their retention probability, such as gene complexity (He and Zhang, 2005), gene length , essentiality (He and Zhang, 2006), expression level (Seoighe and Wolfe, 1999), evolutionary rates , number of protein interactions (Guan et al, 2007;Hakes et al, 2007), functional category (Blanc and Wolfe, 2004), alternative splicing status (Kopelman et al, 2005), protein structure (Papp et al, 2003;Liang et al, 2008), position in the protein-protein interaction network Wu and Qi, 2010), and number of phosphorylation sites (Amoutzias et al, 2010). However, it is unlikely that merely one or two features alone can account for the evolutionary process of duplicated genes, as many of these features are correlated to each other.…”
mentioning
confidence: 99%